Fade slope modeling at high elevation angle on space-earth path link - Dao, Hassan; Islam, Md. Rafiqul; Al-Khateeb, Khalid A. Saeed; Ismail, A.F.; Khan, Sheroz (2012)
Rain fade slope is very useful knowledge used to design of the fade countermeasures in satellite communication link. Recently, ITU-R has proposed fade slope model by limiting elevation angle up to 500. Rain fade slope was measured from downlink of space-earth path of MEASAT3 in Kuala Lumpur (3.30 N, 101.70 E), Malaysia for one year period during 1st July 2010 – 30th June 2011. The elevation angle is about 770. This paper has investigated ITU-R model using measured data. A modified ITU-R model has been proposed for higher elevation angle based on measured data.